2020
DOI: 10.1016/j.jaci.2019.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Long-term air pollution exposure is associated with increased severity of rhinitis in 2 European cohorts

Abstract: Background: Very few studies have examined the association between long-term outdoor air pollution and rhinitis severity in adults. Objective: We sought to assess the cross-sectional association between individual long-term exposure to air pollution and severity of rhinitis. Methods: Participants with rhinitis from 2 multicenter European cohorts (Epidemiological Study on the Genetics and Environment on Asthma and the European Community Respiratory Health Survey) were included. Annual exposure to NO 2 , PM 10 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
3
32
0
1
Order By: Relevance
“…Overweight and obesity are not associated with AR 17 . Of note, many of these exposures and lifestyle risk factors have not been established as major risk factors for AR 18 ; for example, ambient air pollution and passive smoking do not seem to have a large effect on AR development, but pollution may be associated with increased AR severity 19 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Overweight and obesity are not associated with AR 17 . Of note, many of these exposures and lifestyle risk factors have not been established as major risk factors for AR 18 ; for example, ambient air pollution and passive smoking do not seem to have a large effect on AR development, but pollution may be associated with increased AR severity 19 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Very recently, damaging factors that jeopardize the normal development or disturb the balance of an established immune system have come into the focus of research on allergic diseases. Environmental changes caused by in-and outdoor pollution (20,21) and the global warming impact the atopic epidemic and some attempts were undertaken recently to integrate these scenarios into the concept of the Hygiene Hypothesis on the basis of epigenetic changes driven by gene-by-environment interactions (22).…”
Section: Challenges From Changing Environments -Can Epigenetics Provimentioning
confidence: 99%
“…The first study about the effect of long-term PM exposure and rhinitis incidence in adults was published in 2018: data from two European cohort studies did not show any association between annual exposure to NO 2 , PM 10 and PM 2.5 at the participants' home addresses and rhinitis incidence reported by the subjects [39]. Differently, the same authors later on observed that, among participants with no allergic sensitization, increase in NO 2 , PM metrics and traffic exposure were linked to an increased severity score of rhinitis with an exposure-response relationship; differently, among participants with allergic sensitization, increase in air pollution exposure was associated with an increased severity score of rhinitis only for PM 2.5 [40].…”
Section: Discussionmentioning
confidence: 92%
“…Relatively few studies evaluated the link between air pollution and rhinitis [38][39][40]. The first study about the effect of long-term PM exposure and rhinitis incidence in adults was published in 2018: data from two European cohort studies did not show any association between annual exposure to NO 2 , PM 10 and PM 2.5 at the participants' home addresses and rhinitis incidence reported by the subjects [39].…”
Section: Discussionmentioning
confidence: 99%